Pediatric nurse´s work process: a reality to be transformed - Tânia Maria Coelho Leite; Maria Silvia Teixeira Giacomasso Vergílio; Eliete Maria Silva (Universidade Federal do Ceará, 2017)
to analyze the work process of the pediatric nurse, focusing on the hospitalized child. Methods: this is a qualitative research with 17 nurses of a university public hospital, performed by semi-structured interview and participant observation. The analysis of the data content was based on the referential of the work process in health. Results: the actions of the pediatric nurse indicate that their work is far from the planning of integral and humanized care for the children. It is developed from the biomedical model, predominating technical activities, subordinated to the medical work. The systematization of nursing care is incomplete, and humanizing strategies are rarely used. Conclusion: the work process of the pediatric nurse incorporates little strategies that involve children and parents in the treatment. The nurse is not clear about the complexity of her work object, the hospitalized child, to plan comprehensive actions in their entirety.